Retrieval of Lost IUCD from Sigmoid Colon by Colonoscopy: A Case Report - Rashid, Fahmida; Paul, Binoy; Siddique, Nargis; Khanam, Shireen Akhter; Sattar, Md Abdus (Journal of Bangladesh College of Physicians and Surgeons, 2023)
IUCDs are easy to use and effective. It has somewhat greater failure rates than oral contraceptives but is otherwise safe. IUCD is used by 85 million women worldwide. A missing device may indicate unrecognised string expulsion or retraction into the cervix/uterus or IUCD perforation at an extra uterine region. Many problems are observed with IUCD. If IUCD perforates the uterine wall and enters the peritoneal cavity, consequences may be asymptomatic or severe. We report a case of a lost IUCD found trapped in the sigmoid colon wall 4 years after insertion and presenting with chronic constipation in a 23-year-old woman. A CT scan of the abdomen was performed to identify constipation and chronic backache. The IUCD was collected during colonoscopy after bowel preparation. The patient recovered without difficulties. Due to its peculiar presentation, missing IUCD may not require extensive workup. In this rare case, the endoscopic method of retrieving IUCD saved the patient from a main laparotomy. J Bangladesh Coll Phys Surg 2023; 41(4): 315-319